Reference Points, Social Norms, and Fairness in Contract Renegotiations - Björn Bartling; Klaus Schmidt (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Do contracts provide reference points that affect ex post behavior? We address this question in a canonical buyer-seller relationship with renegotiation. Our paper provides causal experimental evidence that an initial contract has a highly significant and economically important impact on renegotiation behavior that goes beyond the effect of contracts on bargaining threatpoints. We compare situations in which an initial contract is renegotiated to strategically equivalent bargaining situations in which no ex ante contract was written. The ex ante contract causes sellers to ask for markups that are 45 percent lower than in strategically equivalent bargaining situations without an initial contract. Moreover, buyers are more likely to reject given markups in renegotiations than in negotiations. We do not find that these effects are stronger when the initial contract is concluded under competitive rather than monopolistic conditions.
Keywords: C78; C91; D03; 330